Transition-Metal-Free Base-Controlled C−N Coupling Reactions: Selective Mono Versus Diarylation of Primary Amines with 2-Chlorobenzimidazoles; Advanced Synthesis and Catalysis; Vol. 363, iss. 5 - Wei Sang; Yan-Yan Gong; Hua Cheng; Rui Zhang; Ye Yuan; Guang-Gao Fan; Zhi-Qin Wang; Cheng Chen; Verpoort F. V. K. Frensis Valter Kornelius (2021, 2021)
Title screen